Gene fusion analysis in renal cell carcinoma by FusionPlex RNA‐sequencing and correlations of molecular findings with clinicopathological features. Issue 1 (2nd September 2019) - Tretiakova, Maria S.; Wang, Wenjing; Wu, Yu; Tykodi, Scott S.; True, Lawrence; Liu, Yajuan J.
Abstract: Translocation renal cell carcinoma (tRCC) affects younger patients and often presents as advanced disease. Accurate diagnosis is required to guide clinical management. Here we evaluate the RNA‐sequencing FusionPlex platform with a 115‐gene panel including TFE3 and TFEB for tRCC diagnosis and correlate molecular findings with clinicopathological features. We reviewed 996 consecutive RCC cases from our institution over the preceding 7 years and retrieved 17 cases with histological and immunohistochemical features highly suggestive of either TFE3 (n = 16) or TFEB (n = 1). Moderate to strong labeling for TFE3 was present in 15 cases; two cases with weak TFE3 expression were melan‐A or cathepsin‐K positive. RNA‐sequencing detected gene rearrangements in eight cases: PRCC‐TFE3 (3), ASPSCR1‐TFE3 (2), LUC7L3‐TFE3 (1), SFPQ‐TFE3 (1), and a novel SETD1B‐TFE3 (1). FISH assays of 11 tumors verified six positive cases concordant with FusionPlex analysis results. Two other cases were confirmed by RT‐PCR. FusionPlex was superior to FISH by providing precise breakpoints for tRCC‐related genes in a single assay and allowing identification of both known and novel fusion partners, thereby facilitating clinicopathological correlations as fusion partners can influence tumor appearance, immunophenotype, and behavior. Cases with partner genes PRCC and novel partner SETD1B were associated with prominent papillary architecture while cases with partner genes ASPSCR1 and LUC7L3 were associated with a predominantly nested/alveolar pattern. The case with SFPQ‐TFE3 fusion was characterized by biphasic morphology mimicking TFEB‐like translocation RCC. We recommend FusionPlex analysis of RCC in patients under age 50 or when the histologic appearance suggests tRCC.